Utilising MIMO for Positioning in Mobile WiMAX Systems - Awang Md Isa, Azmi; Mohamad Isa, Mohd Sa'ari; Haron, Nor Zaidi; Zakaria, Zahriladha; Mohd Zin, Mohd Shahril Izuan (2013)
Worldwide interoperability for microwave access (WiMAX) brings additional features that can be utilized for enhancing positioning accuracy. This paper deals with WiMAX positioning scheme based on the first arrival path (FAP) of the time of arrival (TOA) technique by utilising one of WiMAX offered features i.e multiple input multiple output (MIMO) system. Simulation results show that the performance of system in term of the positioning accuracy adheres to the Federal Communications Commission (FCC) requirements.